PENGARUH DISCOVERY LEARNING TERDADAP HASIL BELAJAR SISWA MATERI USAHA DDAN ENERGI MAN BARUMUN TENGAH - Fatkhul Jannah (Program Studi Pendidikan Fisika, Institut Pendidikan Tapanuli Selatan, 2019)
This study aims to determine the improvement of student physics learning outcomes on work and energy material by using Discovery Learning. Population in this study all students of class XI IPA MAN Barumun Tengah which amounted to 101 students. So the sample of research used is the random sampling. The research method is quasi experiment with two group pretest-posttest design research. Researcher specify which become experiment class in this research is class X1IPA 2 and control class in this research is class XI IPA 3. Technique of collecting data using observation and test, While data analysis using t-test. Based on the calculation, Discovery Learning material work and energy obtained an average value of 88.88% is in the category of